Caffeine improves text reading and global perception. (March 2020) - Franceschini, Sandro; Lulli, Matteo; Bertoni, Sara; Gori, Simone; Angrilli, Alessandro; Mancarella, Martina; Puccio, Giovanna; Facoetti, Andrea
Background: Reading is a unique human skill. Several brain networks involved in this complex skill mainly involve the left hemisphere language areas. Nevertheless, nonlinguistic networks found in the right hemisphere also seem to be involved in sentence and text reading. These areas do not deal with phonological information, but are involved in verbal and nonverbal pattern information processing. The right hemisphere is responsible for global processing of a scene, which is needed for developing reading skills. Aims: Caffeine seems to affect global pattern processing specifically. Consequently, our aim was to discover if it could enhance text reading skill. Methods: In two mechanistic studies ( n =24 and n =53), we tested several reading skills, global and local perception, alerting, spatial attention and executive functions, as well as rapid automatised naming and phonological memory, using a double-blind, within-subjects, repeated-measures design in typical young adult readers. Results: A single dose of 200 mg caffeine improved global processing, without any effect on local information processing, alerting, spatial attention and executive or phonological functions. This improvement in global processing was accompanied by faster text reading speed of meaningful sentences, whereas single word/pseudoword or pseudoword text reading abilities were not affected. These effects of caffeine on reading ability were enhanced by mild sleep deprivation. Conclusions: These findings show that a small quantity of caffeine could improve global processing and text reading skills in adults.